2016
DOI: 10.1158/1538-7445.am2016-2644
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 2644: AP32788, a potent, selective inhibitor of EGFR and HER2 oncogenic mutants, including exon 20 insertions, in preclinical models

Abstract: In non-small cell lung cancer (NSCLC), multiple classes of activating mutations have been identified in EGFR and HER2 that vary widely in their sensitivity to available tyrosine kinase inhibitors (TKIs). Erlotinib, gefitinib, and afatinib are approved for use in patients with the most common forms of EGFR activating mutations (ie, exon 19 deletions or L858R substitutions). However, no TKIs are approved for patients with EGFR activated by any other mutation, including exon 20 insertions or other uncommon substi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 0 publications
0
30
0
Order By: Relevance
“…We initiated a multi-center phase II trial (NCT02834936) afterwards, currently in progress. Recently, it was released that poziotinib and TAK-788 (AP32788) also showed promising results in preclinical model together with early clinical setting [28,29], despite only one PR in HER2 mutation cohort in TAK-788 dose-escalation phase [30]. Jang et al [31] also reported a new HER2 Ex20Ins mutant inhibitor that was highly potent in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…We initiated a multi-center phase II trial (NCT02834936) afterwards, currently in progress. Recently, it was released that poziotinib and TAK-788 (AP32788) also showed promising results in preclinical model together with early clinical setting [28,29], despite only one PR in HER2 mutation cohort in TAK-788 dose-escalation phase [30]. Jang et al [31] also reported a new HER2 Ex20Ins mutant inhibitor that was highly potent in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Dacomitinib has shown activity in ERBB2-mutated NSCLC [24], as has neratinib [25], with more trials of this agent still ongoing alone and in combination with other agents (NCT01827267, NCT01953926, NCT02593708). Another ERBB2 TKI, AP32788, shows promise in preclinical studies involving ERBB2 exon 20 insertion mutant cancer cell lines [26], and a clinical trial is ongoing (NCT02716116). Potential activity of ado-trastuzumab emtansine is also intriguing; while our treated patient did not respond to the medication, there has been one case report showing response to the medication in a patient with ERBB2 exon 20 insertion mutation, overexpression and amplification [27].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, classification of loss-of-function PTEN alterations as a Level 4 alteration indicates that patients with PTEN-deficient tumors would be rational candidates for a clinical trial of investigational PI3-kinase pathway inhibitors alone or in combination with other agents, but that the use of such agents outside the context of a clinical trial is not yet supported by the sum of the clinical data. Additional examples of Level 4 alterations include NF1 inactivating alterations, which may be predictive of response to MEK1/2 inhibitors 40 , and EGFR exon 20 insertions in lung adenocarcinomas that respond poorly to erlotinib 41,42 , but which may be sensitive to AP32788, an investigational inhibitor of EGFR and HER2 43 (Fig. 3).…”
Section: The Oncokb Frameworkmentioning
confidence: 99%